2020
DOI: 10.1055/s-0039-3401992
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis

Abstract: Mucormycosis is an infection caused by a group of filamentous molds within the order Mucorales. Infections may result from ingestion of contaminated food, inhalation of spores into the nares or lungs, or inoculation into disrupted skin or wounds. In developed countries, mucormycosis occurs primarily in severely immunocompromised hosts (e.g., those with hematological malignancies, organ transplantation, neutropenia, autoimmune disorders, or other impairments in immunity). Only 6 to 10% of cases occur in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 228 publications
(419 reference statements)
1
108
0
5
Order By: Relevance
“…The clinical presentations of mucormycosis are classified on the basis of anatomic localisation, such as rhino-orbital-cerebral (ROCM), pulmonary, gastrointestinal, cutaneous, renal, and disseminated mucormycosis [ 2 , 3 ]. Patients with diabetes mellitus, haematological malignancy and chemotherapy, haematopoietic stem cells, and solid-organ transplant recipients on immunosuppressive therapy, with iron overload, on peritoneal dialysis, extensive skin injury, human immunodeficiency virus (HIV) infection, and voriconazole therapy are at increased risk of acquiring mucormycosis [ 2 , 3 , 4 ]. A considerable number of mucormycosis cases are reported in immunocompetent hosts [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentations of mucormycosis are classified on the basis of anatomic localisation, such as rhino-orbital-cerebral (ROCM), pulmonary, gastrointestinal, cutaneous, renal, and disseminated mucormycosis [ 2 , 3 ]. Patients with diabetes mellitus, haematological malignancy and chemotherapy, haematopoietic stem cells, and solid-organ transplant recipients on immunosuppressive therapy, with iron overload, on peritoneal dialysis, extensive skin injury, human immunodeficiency virus (HIV) infection, and voriconazole therapy are at increased risk of acquiring mucormycosis [ 2 , 3 , 4 ]. A considerable number of mucormycosis cases are reported in immunocompetent hosts [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate with localized cutaneous mucormycosis is 10% to 30%, whereas disseminated mucormycosis carries a much higher rate (50% to 90%), depending upon organ involvement [ 9 11 ]. One study comparing treatment modalities indicated that the lowest mortality rate was associated with amphotericin B plus surgery (18.8% to 43.7%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some pulmonary and gastrointestinal mucormycosis cases have also been reported (do Monte et al, 2020;Garg et al, 2021). The exact cause of increased mucormycosis infection cases in COVID-19 patients is still unknown, but certain factors could have played the role, such as; immunocompromised conditions due to the pre-existing diseases, immunosuppressive drug therapy, immune alterations by the SARS-CoV-2, and pre-existing poor lung conditions (Reid et al,2020). In India, people have also used cow dung as a part of treatment for Covid-19.…”
Section: Main Textmentioning
confidence: 99%